A transparent universal health coverage index with decomposition by socioeconomic groups: Application in Asian and African settings - Khan, Jahangir A. M.; Ahmed, Sayem; Chen, Tao; Tomeny, Ewan M.; Niessen, Louis W. (Springer Nature, 2022)
This article was published in the Applied Health Economics and Health Policy [© Springer Nature Switzerland AG 2019] and the definite version is available at: http://dx.doi.org/10.1007/s40258-019-00464-9 The Journal's website is at: https://link.springer.com/article/10.1007/s40258-019-00464-9#citeas